Socioeconomic inequalities and the COVID-19 pandemic in France: Territorial analyzes based on epidemic wave and metropolitan area - Luka Canton; Pierre Schalkwijk; Jordi Landier; Stanislas Rebaudet; Émilie Mosnier; Pascal Handschumacher; Stève Nauleau; Philippe Malfait; Ludivine Launay; Cyrille Delpierre; Michelle Kelly-Irving; Sabira Smaili; et al. (PLoS ONE, 2026)
Background Previous studies have highlighted the relationship between socioeconomic inequalities and the general population’s risk of contracting or dying from COVID-19 during the 2020−2023 pandemic. In France, socioeconomic inequalities vary across metropolitan areas; few studies have investigated whether this variation explains the spatial disparities observed in COVID-19 incidence and testing rates during the pandemic. We examined the relationship between socioeconomic profiles and these two rates across all 22 metropolitan areas in France for eight of the country’s nine epidemic waves. Methods For each metropolitan area, we used socioeconomic variables from census data to define socioeconomic profiles through principal component clustering. We then used spatialized generalised additive mixed models to analyze associations between these profiles and both testing and incidence rates, for each epidemic wave from July 2020 to March 2023. Finally, we performed meta-regressions to study the distribution of testing and incidence rate ratios among the various socioeconomically deprived and privileged profiles within each of the 22 metropolitan areas, according to COVID-19 vaccination rate. Results Testing rates were lower in socioeconomically deprived metropolitan areas than in privileged ones, except during wave 4 (July-October-2021), when testing rates were more similar. Incidence rates were higher in deprived areas (waves 2–4, July-2020 to October-2021), but this pattern reversed between waves 6–9 (March-2022 to March-2023). Meta-regressions indicated that high vaccination coverage was associated with a narrower gap in testing between deprived and privileged areas. Moreover, for each metropolitan area, the higher the level of deprivation in a zone within the deprived profile, the greater the deprived-privileged gap in under-testing. Conclusions The impact of socioeconomic inequalities on testing and incidence patterns during the COVID-19 pandemic in each metropolitan area in France was driven by the most deprived zones; this impact varied across epidemic waves. Higher vaccination rates and government health measures (lockdowns, mandatory health pass) may have reduced this variation.